In this question, the following was shown:

If $R(z)=\dfrac{P(z)}{Q(z)}$, where $P,Q$ are polynomials in a complex variable $z$, satisfies the condition that $|R(z)|=1$ whenever $|z|=1$, then the identity $R(z)\overline{R(1/\overline{z})}=1$ holds for all complex $z$.

The proof given there uses the identity theorem. Since I'm not familiar with the theorem yet, I would like to find an easier approach.

So I try direct substitution. Writing $P(z)=a_nz^n+a_{n-1}z^{n-1}+\ldots+a_0$ and $Q(z)=b_mx^m+b_{m-1}x^{m-1}+\ldots+b_0$, we find that $$R(z)=\frac{P(z)}{Q(z)}=\frac{a_nz^n+a_{n-1}z^{n-1}+\ldots+a_0}{b_mz^m+b_{m-1}z^{m-1}+\ldots+b_0}$$ and $$\overline{R(1/\overline{z})} = \frac{\overline{P(1/\overline{z})}}{\overline{Q(1/\overline{z})}} = \frac{\overline{a_n}+\overline{a_{n-1}}z+\ldots+\overline{a_0}z^n}{\overline{b_m}+\overline{b_{m-1}}z+\ldots+\overline{b_0}z^m}\cdot z^{m-n}$$

So the identity $R(z)\overline{R(1/\overline{z})}=1$ that we wants to prove can be turned into $$z^{m-n}(a_nz^n+a_{n-1}z^{n-1}+\ldots+a_0)(\overline{a_0}z^n + \ldots + \overline{a_{n-1}}z + \overline{a_n}) = (b_mz^m+b_{m-1}z^{m-1}+\ldots+b_0)(\overline{b_0}z^m+\ldots+\overline{b_{m-1}}z+\overline{b_m}).$$ where we have the condition that for any $|z|=1$, $$|a_nz^n+a_{n-1}z^{n-1}+\ldots+a_0| = |b_mz^m+b_{m-1}z^{m-1}+\ldots+b_0|.$$

How can we proceed from here?

  • 2
    $\begingroup$ You mean a more elementary approach. This way is definitely not easier. $\endgroup$ – Cocopuffs Aug 25 '13 at 1:12
  • $\begingroup$ Kinda weird, seeing the algebra-precalculus and complex-analysis tags on the same question. $\endgroup$ – Gerry Myerson Aug 25 '13 at 1:14
  • $\begingroup$ I don't think your equation about the conjugate of R is correct. The conjugate is both on R and on 1/z ,but not on the coefficients of P and Q. $\endgroup$ – Betty Mock Aug 25 '13 at 2:18

If we denote $$\sum_{k=0}^n \overline{a_k}z^{n-k} = z^n\overline{P(1/\overline{z})}$$ by $P^\ast(z)$, and similar for $Q$, the identity

$$R(z) \cdot \overline{R(1/\overline{z})} = 1, \quad \lvert z\rvert = 1$$


$$z^mP(z)P^\ast(z) = z^nQ(z)Q^\ast(z)$$

for $\lvert z\rvert = 1$, in other words, the polynomial

$$z^mP(z)P^\ast(z) - z^nQ(z)Q^\ast(z)$$

has infinitely many zeros, hence is the zero polynomial.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.